Multivariate selection and intersexual genetic constraints in a wild bird population. (14th July 2016) - Poissant, J.; Morrissey, M. B.; Gosler, A. G.; Slate, J.; Sheldon, B. C.
Abstract: When selection differs between the sexes for traits that are genetically correlated between the sexes, there is potential for the effect of selection in one sex to be altered by indirect selection in the other sex, a situation commonly referred to as intralocus sexual conflict (ISC). While potentially common, ISC has rarely been studied in wild populations. Here, we studied ISC over a set of morphological traits (wing length, tarsus length, bill depth and bill length) in a wild population of great tits ( Parus major ) from Wytham Woods, UK. Specifically, we quantified the microevolutionary impacts of ISC by combining intra‐ and intersex additive genetic (co)variances and sex‐specific selection estimates in a multivariate framework. Large genetic correlations between homologous male and female traits combined with evidence for sex‐specific multivariate survival selection suggested that ISC could play an appreciable role in the evolution of this population. Together, multivariate sex‐specific selection and additive genetic (co)variance for the traits considered accounted for additive genetic variance in fitness that was uncorrelated between the sexes (cross‐sex genetic correlation = −0.003, 95% CI = −0.83, 0.83). Gender load, defined as the reduction in a population's rate of adaptation due to sex‐specific effects, was estimated at 50% (95% CI = 13%, 86%). This study provides novel insights into the evolution of sexual dimorphism in wild populations and illustrates how quantitative genetics and selection analyses can be combined in a multivariate framework to quantify the microevolutionary impacts of ISC.